Residual root extraction in a hypertensive and diabetic patient: case report (Research, Society and Development, 2022)
Residual root is a tooth remnant that is retained in the bone, without the crown, and may or may not be visible. The extraction of residual roots is extremely important since patients with residual roots can complain about some factors, such as; pain when chewing, presence of bad breath and local pain. An increasing number of patients with systemic alterations have sought clinical dental care. Among the systemic changes, the main ones are; Diabetes Mellitus and Hypertension. The objective of this study is to report a clinical case of a 73-year-old male patient, who uses antihypertensive drugs, anticoagulants and insulin and who has an indication for extraction of the residual root of tooth 13. For this case, the method selected, the extraction was performed using the third technique, since the patient had no remaining tooth for the use of forceps. The exeresis was performed using the Seldin extractors as a noble instrument. It was possible to conclude that hypertensive and diabetic patients should receive differentiated dental treatment, with greater attention to anamnesis and care protocol so that it is possible to obtain satisfactory results.